Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Dengan Corporate Social Responsibility Sebagai Variabel Moderating - Rizki Novita Damayanti; Hudi Kurniawanto (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of the following research to see the effect GCG represented in managerial share ownership, institutional share ownership, commissioner size as well as independent commissioners on financial performance in companies with CSR as moderating. The following research is quantitative, the data needed is financial statements of manufacturing companies in bei 2020-2022. data used is secondary. Sampling process uses purposive sampling techniques to obtain sample of 34 companies. Data analysis techniques with multiple linear regression analysis and absolute difference value testing. The results illustrate that managerial ownership and institutional ownership have no significant effect on financial performance in the company, commissioner size has a positive and significant effect on financial performance in company and independent commissioners have a negative and significant effect on financial performance in company. While in absolute difference value test with the results that csr has not been able to moderate the effect of managerial share ownership and institutional share ownership on financial performance in company, but csr can moderate the effect of commissioner size and independent commissioners on financial performance in company.